Startup Accelerator Returns: J Curve or L Curve? A Comparative Performance Analysis Between a Venture Accelerator and Early-Stage Venture Capital - Aleš Pustovrh (Economic and Business Review)
This document analyses the profitability of investments in venture accelerators compared to early-stage venture capital funds. Using a case study of a single fund manager operating both investment types, it tracks the Total Value to Paid-In (TVPI) ratio over 6 years. The early-stage venture capital investments showed a positive trend, exceeding a TVPI of 1, indicating profitability driven by company survival rates, external funding attraction, and growth. Conversely, the accelerator investments underperformed, with a TVPI consistently below 1, suggesting a loss for investors. This raises questions about the long-term viability of the accelerator model, potentially resulting in an L curve rather than the expected J curve of returns. While the accelerator's performance could still improve if the few successful companies significantly outperform the underperforming majority, this reliance on a small number of successes represents an inherently higher risk for investors. Future research should incorporate broader datasets and consider various market dynamics to generalize the findings, utilizing panel data across different geographies and industries.